Dioxin-like activity of brominated dioxins as individual compounds or mixtures in in vitro reporter gene assays with rat and mouse hepatoma cell lines. (October 2017) - Suzuki, G.; Nakamura, M.; Michinaka, C.; Tue, N.M.; Handa, H.; Takigami, H.
Abstract: In vitro reporter gene assays detecting dioxin-like compounds have been developed and validated since the middle 1990's, and applied to the determination of dioxin-like activities in various samples for their risk management. Data on characterizing the potency of individual brominated dioxins and their activity in mixture with chlorinated dioxins are still limited on the cell-based assay. This study characterized the dioxin-like activities of the 32 brominated dioxins, such as polybrominated dibenzo- p -dioxins, polybrominated dibenzofurans (PBDFs), coplanar polybrominated biphenyls, mixed halogenated dibenzo- p -dioxins and dibenzofurans (PXDFs), as a sole component or in a mixture by DR-CALUX (dioxin-responsive chemically activated luciferase expression) using the rat hepatoma H4IIE cell line and XDS-CALUX (xenobiotic detection systems–chemically activated luciferase expression) assays using the mouse hepatoma H1L6.1 cell line. The 2, 3, 7, 8-TCDD-relative potencies (REPs) of most of the brominated dioxins were within a factor of 10 of the WHO toxicity equivalency factor (WHO-TEF) for the chlorinated analogues. The REPs of a few PXDFs were an order of magnitude higher than the corresponding WHO-TEFs, indicating their toxicological importance. Results with reconstituted mixtures suggest that the activity of brominated and chlorinated dioxins in both CALUX assays was dose-additive. Thus, obtained results indicated the applicability of the CALUX assays as screening tools of brominated dioxins together with their chlorinated analogues. Highlights: We evaluated dioxin-like activity of brominated dioxins with CALUX assays. Updated REPs of brominated dioxins were within a factor of 10 of the WHO-TEF. Brominated and chlorinated dioxins in mixtures were dose-additive on CALUX assays. CALUX assays can be applied for determination of both dioxins in various samples.